In Well‐Treated Celiac Patients Low‐Level Mucosal Inflammation Predicts Response to 14‐day Gluten Challenge. Issue 4 (4th January 2021) - Stamnaes, Jorunn; Stray, Daniel; Stensland, Maria; Sarna, Vikas K.; Nyman, Tuula A.; Lundin, Knut E. A.; Sollid, Ludvig M.
Abstract: In celiac disease (CeD), gluten activates adaptive immune cells that cause damage to the small intestinal mucosa. Histological evaluation of intestinal biopsies allows for grading of disease severity. CeD can effectively be treated with a life‐long gluten‐free diet. Gluten challenge of treated CeD patients is used to confirm diagnosis and to test drug efficacy in clinical trials, but patients respond with different magnitudes to the same gluten challenge. In this study of 19 well‐treated CeD patients, proteome analysis of total tissue or isolated epithelial cell compartment from formalin‐fixed paraffin embedded biopsies collected before and after 14‐day gluten challenge demonstrates that patients with strong mucosal response to challenge have signs of ongoing tissue inflammation already before challenge. This low‐level tissue inflammation at baseline is paralleled by increased gluten specific CD4+ T‐cell frequencies in the gut and presence of a low‐level blood inflammatory profile. Thus, apparently well‐treated CeD is frequently not entirely quiescent, with presence of low‐grade inflammation and antigluten immunity in the gut mucosa. Histology assessment alone appears insufficient to judge full recovery and gut mucosal healing of CeD patients. The findings raise a concern whether a seemingly proper gluten‐free diet is able to curb gut inflammation in all CeD patients. Abstract : Spatially resolved tissue proteome analysis reveals low‐level inflammation and antigluten immunity in gut of some patients that are apparently well‐treated with gluten‐free diet. These patients develop strong mucosal response to short‐term gluten challenge.